Novel cooling channel design of double PV-TEG units by using pilot jets combined with sinusoidal-corrugated object and performance predictions with ANFIS - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2026)
The efficient use of photovoltaic (PV) modules or PV-integrated systems requires innovative cooling strategies. In order to increase the performance of double PV units in conjunction with thermoelectric generators (TEGs), this study aims to develop a unique L-shaped channel cooling system with pilot jets and sinusoidal wavy objects at the channel junctions. The channel flow Reynolds number (Reh between 100 and 500), pilot jet Reynolds number (Rej between 100 and 500), amplitude of corrugation (Amp between 0.01 and 0.15), and wave number of corrugation (Nw between 1 and 5) are all varied in the numerical simulations by using finite element method. The best cooling results for both horizontal channel (H-C) and vertical channel (V-C) are obtained when the wavy object is used at Reh = 500 with the greatest jet flow Re. The use of wavy objects results in additional PV-cell temperature drops of 4 degrees C and 2.5 degrees C for H-PV and V-PV using NF at the lowest Reh, and 4 degrees C and 1.7 degrees C at the maximum Reh. The V-PV cell temperature falls by 4 degrees C and 1.3 degrees C at Reh = 100 and Reh = 500 when Rej is raised from 100 to 500 using NF. Pilot jets and wavy objects are shown to significantly improve the cooling effectiveness of dual PV-TEG combination units. In comparison to the reference scenario (BF, no-object, no-jet at Reh = 100), temperature drops of 13.5 degrees C and 17.4 degrees C for H-PV and V-PV, respectively, are obtained when NF, wavy objects, and pilot-jets are used. The average surface temperature of each PV panel installed in H-C and V-C is estimated using ANFIS (Adaptive-Network Based Fuzzy Inference Systems) by adjusting the pilot jet flow Re and channel flow Re for configurations with and without a wavy object in the cooling channel. Outcomes are useful to develop and optimize efficient cooling solutions for multiple PV arrangements utilized in practice.
Keywords: Wavy object; Pilot jet; PV-TEG units; FEM; ANFIS